2010
DOI: 10.1002/mame.201000270
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Morphology Studies of Thermosets from a Liquid‐Crystalline Epoxy Resin with Biphenol and Aromatic Ester Groups

Abstract: Liquid‐crystalline epoxy thermosets were prepared by adding M1 into DGEBA/DDM blends. M2 was added to DGEBA/DDM to produce thermosets for comparison. The influences of the concentration and chemical structure on the mechanical and thermal properties were investigated systematically. The M1/DGEBA blends possessed increased rubbery plateau modulus, higher glass transition temperatures, and lower tan δ. The use of small amounts of M1 may improve the mechanical properties greatly. Izod notched impact strength coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…4, 4’‐biphenol (DOD) is an organic intermediate with high melting point (281 °C) and good heat resistance, which makes it a common rubber antioxidant and plastic antioxidant. When polyolefin products are processed or applied in high‐temperature conditions, composite additives migrate and get volatilized, resulting in quality degradation or even disqualification . To prevent loss of additives, a lot of measures can be taken, including (1) Blocking method, such as adding flake montmorillonite or adsorbent; (2) Grafting or polymerizing micro‐molecules into polymer; (3) Improving molecular weight of the additive by modifying or polymerizing.…”
Section: Introductionmentioning
confidence: 99%
“…4, 4’‐biphenol (DOD) is an organic intermediate with high melting point (281 °C) and good heat resistance, which makes it a common rubber antioxidant and plastic antioxidant. When polyolefin products are processed or applied in high‐temperature conditions, composite additives migrate and get volatilized, resulting in quality degradation or even disqualification . To prevent loss of additives, a lot of measures can be taken, including (1) Blocking method, such as adding flake montmorillonite or adsorbent; (2) Grafting or polymerizing micro‐molecules into polymer; (3) Improving molecular weight of the additive by modifying or polymerizing.…”
Section: Introductionmentioning
confidence: 99%
“…When the material is subjected to external forces, these mesomorphic domains can withstand and disperse the stress; this hinders crack propagation, and therefore, the material exhibits a high toughness . With their good mechanical properties, chemical resistance, low shrinkage properties during the curing process, and higher fracture toughness compared with general thermosetting resins, LCTs have been developed to improve the mechanical and thermal properties of conventional thermosets and to overcome the drawbacks of other modification methods.…”
Section: Introductionmentioning
confidence: 99%
“…3,3′,5,5′-Tetramethylbiphenyl-4,4′-diylbis(4-(oxiran-2-ylmethoxy) benzoate) ( M1 ) was synthesized with a high efficient and economical method [ 15 ]. Effects on modifying diglycidyl ether of bisphenol A (DGEBA)/4,4′-diaminodiphenyl methane (DDM) revealed that the izod notched impact strength could be enhanced by 55% by the addition of 2% M1 compared to unmodified DGEBA blends [ 16 , 17 ]. With respect to its excellent performance in improving mechanic and thermal properties of ordinary commercial epoxy resin, a good performance on modifyingnylon66 ( M2 ) will be a reasonable expectation.…”
Section: Introductionmentioning
confidence: 99%